Post-activation performance enhancement (PAPE) protocols do not further increase jumping performance beyond warm-up effects: findings from three acute randomized crossover trials - Rappelt, Ludwig; Held, Steffen; Wiedenmann, Tim; Micke, Florian; Donath, Lars (Frontiers in Physiology, 2024)
Post-activation performance enhancement (PAPE) cannot be clearly distinguished from warm-up effects. To disentangle PAPE from a systemic warm-up effect, we conducted three randomized crossover trials (RCT). Each RCT consisted of a familiarization/one-repetition-maximum (1RM) assessment session followed by two interventional sessions (random order). In Study I, 18 participants (age: 26 ± 4 years; height: 1.84 ± 0.06 m; mass: 83.7 ± 8.7 kg; Squat-1RM: 146 ± 19 kg) performed either a 3-second isometric squat at 130%1RM or a 6-second squat at 65%1RM. In Study II, 28 participants (11 female; age: 23 ± 3 years; height: 1.77 ± 0.08 m; mass: 76.5 ± 10.4 kg; Squat-1RM: 109 ± 38 kg) completed either Squat (3x3 repetitions, 85%1RM) or local electromyostimulation of the quadriceps muscle (85% of individual pain threshold). In Study III, 20 participants (6 female, age: 25.0 ± 3.5 yrs, mass: 78.5 ± 15.8 kg, height: 1.75 ± 0.08 m; SQ-1RM: 114 ± 33 kg, chest-press-1RM: 74 ± 29 kg) performed either squats or chest press (4 repetitions, 80%1RM). Counter-Movement-Jump height (CMJ) was assessed after a general (PRE) and/or muscle-specific warm-up (POST_WU) and for up to 11 minutes after the PAPE protocols. To identify possible differences in CMJ between the experimental conditions, mixed-design ANOVA models were used for each study individually, with condition and time modelled as fixed effects, while participants were included as a random effect blocking factor. The level of statistical significance was set at α = 5%. In studies I and II, significant effects for time (p<0.05, ωp2 = 0.06 & p<0.001, ωp2 = 0.43) were found with the highest CMJ compared to all other time points at PRE (≤8.2±4.6%, standardized mean difference: ≤0.39), regardless of condition. In study III, no significant effects were observed. Thus, PAPE protocols do not further improve jumping performance compared to a general and muscle-specific traditional warm-up. Thus, general and sport-specific warm-up strategies prior to tasks requiring explosive strength should be used.